Impact of geriatric co-management programmes on outcomes in older surgical patients: update of recent evidence. Issue 1 (February 2020) - Van Grootven, Bastiaan; Mendelson, Daniel Ari; Deschodt, Mieke
Abstract : Purpose of review: To determine the impact of geriatric co-management programmes on outcomes in older patients undergoing a surgical procedure. Recent findings: Twelve programmes were identified. Time to surgery was decreased in two of four studies [pooled mean difference = −0.7 h (95% CI, −3.1 to 4.4)]. The incidence of complications was reduced in two of seven studies (pooled absolute risk reduction = −4% (95% CI −10 to 2%)). Length of stay was reduced in four of eight studies [pooled mean difference = −1.4 days (95% CI −2.7 to −0.1)]. In-hospital mortality was reduced in one of six studies [pooled absolute risk reduction = −2% (95% CI −4 to −0%)]. Unplanned hospital readmissions at 30 days follow-up was reduced in two of three studies [pooled absolute risk reduction = −3% (95% CI −5 to −0%)]. Summary: There was a shorter length of stay, less mortality and a lower readmission rate. However, there was uncertainty whether the results are clinically relevant and the GRADE of evidence was low. It was uncertain whether the outcomes time to surgery and complications were improved. The evidence is limited to hip fracture patients.